Theory of the age dependence of mortality from congenital defects - Dolejs, J (Mechanisms of ageing and development, 2001)
A theory is presented, based on the evidence that the congenital defect of an individual is at one of many different levels. It is supposed that the individual mortality risk from congenital defect is lognormally or normally distributed in the population. The relationship between childhood mortality from seven congenital defects and age is described. It uses data from the US during the period 1979-1991. Mortality from five congenital defects is inversely proportional to age. Mortality from two congenital defects is inversely proportional to the second power of age. The presented theory explains these two observed types of mortality decline with age. Childhood mortality from some infectious diseases is also inversely proportional to age during childhood in different populations. It follows from this theory that the death from these infectious diseases up the age of 10 years may be caused by a hidden congenital frailty.
Keywords: Child; Female; Aging; Models, Biological; Congenital Abnormalities; infekční nemoci; Communicable Diseases; stárnutí; Humans; ženské pohlaví; vrozené vady; mužské pohlaví; lidé; Male; dítě; biologické modely